The Impact of Information-Based Family Planning Counseling on IUD Adoption as a Long-Term Contraceptive - Mardi, Indrawahyuni; Ismawati, Ismawati; Astuti, Astuti; Zulhaedah, Zulhaedah; Kasmawati, Kasmawati (Utan Kayu Publishing, 2024)
Regulating the interval between pregnancies is crucial to preventing maternal and infant mortality. The National Population and Family Planning Agency (BKKBN) recommends delaying pregnancies to support women of reproductive age in achieving healthier maternal outcomes. However, limited interest in using Intrauterine Devices (IUD) is influenced by factors such as knowledge and attitudes. This study aims to evaluate the impact of IUD family planning counseling on attitudes and interests among prospective family planning acceptors. This quantitative study employs a quasi-experimental one-group pretest-posttest design. The study population included 55 postpartum mothers, with a sample of 51 participants selected through purposive sampling. Data analysis was conducted using the Nonparametric Wilcoxon Test. Results revealed a statistically significant improvement in attitudes (p-value = 0.000) and interest (p-value = 0.000) following counseling, as indicated by increased mean scores from 21.75 to 27.61 for attitudes and 9.28 to 13.73 for interest. These findings demonstrate that IUD counseling effectively enhances positive attitudes and interest in using long-term contraceptive methods. The study concludes that comprehensive IUD counseling is essential in increasing acceptance of IUD as a contraceptive method. The findings suggest that healthcare providers should adopt tailored, evidence-based counseling approaches to overcome misconceptions and foster supportive environments for women, including engaging family members, particularly spouses. These efforts can contribute to reducing maternal and infant mortality rates through informed contraceptive choices.